Mary I. Ingraham, Joseph K. So, and Roy Moodley, eds. 2016. Opera in a Multicultural World: Coloniality, Culture, Performance. New York: Routledge - Forner, Jane (Current Musicology, 2018)
Opera scholars have had something of a bounty in recent years. Opera in a Multicultural World: Coloniality, Culture, Performance follows in a line of collected volumes that have sought to diversify the field through critical focuses on race, identity, colonialism, and gender, including Opera Indigene: Re/presenting First Nations and Indigenous Cultures (2011, edited by Pamela Karantonis and Dylan Robinson), Blackness in Opera (2012, edited by Naomi André, Karen Bryan, and Eric Saylor), and Masculinity in Opera (2013, edited by Philip Purvis). Such works are foundational to the present volume through their emphatic efforts not only to bring these issues to the forefront and consolidate academic work scattered across (and separated by) disciplinary and historical boundaries, but also for their expansion of operatic methodologies. Chapters written by performers and composers sit alongside traditional analyses, bringing into dialogue a welcome diversity of perspectives and conceptual approaches. Uniting seemingly disparate objects of study around common themes, Opera in a Multicultural World promises much: multiculturalism, coloniality, culture, genre, and performance are all touched upon, though condensed to the space of only a few hundred pages. While, like the aforementioned volumes, the book suffers slightly from this topical magnitude, such collections have brought to attention both the enormous potential scope for further work and the clear benefits of multi-disciplinary approaches. Indeed, given the three editors’ contrasting disciplinary backgrounds—musicology, anthropology, and psychology—it is clear that amalgamating and juxtaposing historical, analytical, and sociological research approaches has been a positive influence in shaping the present volume. Synthesizing and building on the existing diverse strands of writing on opera that foreground issues of race and cultural identity remains a pressing need that such volumes have begun to address. Whereas significant texts emerging from feminist scholarship of the 1960s and 1970s, such as Catherine Clément’s seminal Opera, or the Undoing of Women (1979), paved the way for many subsequent studies on gender in opera, a critical mass of academic writing on race in opera has until recently lacked consistency. Collections like those mentioned above, and more work appearing since the publication of Opera in a Multicultural World, bring together wide-ranging approaches to a tremendously varied repertoire into a generally cohesive space. Weaving together these disparate strands requires a lot from both authors and readers—examining opera’s position in articulating social realities and identities within several problematic frameworks is a significant undertaking. It can be a struggle to present analyses of specific works that successfully unite around multiple larger theoretical constructs while simultaneously maintaining a focus on topics of social exclusion, access, and privilege in opera as commerce alongside the legacy of colonialism in music and scholarship. André’s recently published book Black Opera (2018), for instance, successfully expands on topics raised in Blackness in Opera with an in-depth study of race and operatic history, demonstrating the value of specialized as well as broader volumes. There is not space within this review to adequately discuss each of the twelve chapters and the introduction in detail; rather, I will draw out some of the ways in which the book’s central themes emerge in different analytical contexts, focusing in greater detail on a selection of essays. As in any edited collection, some are stronger than others, but all present interesting and worthwhile research. The fundamental premise of the volume is enmeshed with the fraught position of multiculturalism in today’s global political landscape: there is a great deal at stake in a concept that fundamentally deals with competing notions of how to co-exist within increasingly diverse societies. Philosophical, historical, and sociological understandings of approaches to society which are often rooted in colonial history are hotly contested in the public media and political spheres as much as within academic walls. As a concept, policy, and practice, multiculturalism is both vitally relevant to contemporary society and epistemologically fragile. With this in mind, a reader expects that the editors, if not every author, will present a theoretical framework of the multicultural as it might apply to opera. The introduction does touch on the significantly shifting approaches to the concept in the last two decades, for which Fred Constant’s Le Multiculturalisme (2000) was a catalyst. A brief passage on Constant notes a trend familiar to recent generations of musicologists and music theorists: the rejection of binary oppositions in critical thought, in this case between “diversity” and “unity”: Constant suggests that multiple cultures coexist within communities or nations and individuals frequently—and concurrently—may experience both “pluralism” and “assimilation.” Audience experiences of operatic productions across time and space similarly engender varied interpretations. (5) It is evident from the considerable focus on productions and audiences that the multiplicity of ways of experiencing opera and fluidity of meaning is a crucial part of the guiding vision of the collection. One feels somewhat ill-equipped, however, to contemplate the ensuing essays with the limited space devoted in the introduction to elucidating the concept of multiculturalism and how it might apply in an operatic context. The book is divided into three parts, titled “Opera as Tradition,” “Critical Case Studies,” and “Opera in the Real World.” The first two deal more concretely with methodologies, individual operatic works, specific performances or productions, and historical events; the third part expands the purview to librettists, performers, and audiences. Part one features some of the most successful essays in relation to the apparent intentions of the volume as a whole. Linda and Michael Hutcheon’s chapter “Jazz, Opera, and the Ideologies of Race” synthesizes some strands of their prior work on opera, race, postcolonialism, and identity in Canada (Hutcheon, 1991; Hutcheon and Hutcheon, 1998). The essay examines the complex intersections between contemporary Canadian multiculturalism and colonial and postcolonial memory, as well as issues of genre and performance, in three recent operas: Beatrice Chancy (1998), with music by James Rolfe, and Québécité (2003) and Trudeau: Long March/Shining Path (2010), both with music by D.D. Jackson. The libretti for Beatrice Chancy and Québécité were penned by the celebrated Africadian—to use his own term—poet and author George Elliott Clarke, who also features as a contributor to the volume (chapter 12). Reading these two chapters together offers a dialogue between artists and academics that is still rare even in scholarship on contemporary operas, where interviews often figure prominently. The Hutcheons examine these operas as “a specifically Canadian version of the multicultural” (32), describing Beatrice Chancy as a “postcolonial opera as well as a response to continuing coloniality” (25). Clarke himself has written extensively elsewhere about the capacity of the opera to resonate far beyond its appearance as a quasi-historical drama, intended to reflect and explore Canadian society across temporal and ethnic bounds (Clarke, 1997; Domínguez and Clarke, 2001; Clarke, 2002). This is evident especially in the longer printed version of the libretto, in which images from historical and modern archives are interpolated amid the text (Clarke, 1999). Conceiving of these operas as representing a mode of articulating difference on stage that is temporally and geographically specific, the authors examine the works in tandem with issues of production and performance. Tantalizing phrases abound, but are often left uninterrogated, such as “the postcolonial here became the multicultural” (31), referring to the blend of jazz idioms with South Asian and Punjabi musical styles in Québécité, whose dramatis personae feature two mixed-race couples in Québec City. Each opera’s distinctive musical palate emerges clearly—the mix of blues, Scottish fiddle music, bel canto, and ring shouts in Beatrice Chancy, for instance—but a more thorough musical analysis, one that might present sound and signification in relation to the central questions of (post)coloniality and multiculturalism, is lacking. Aspects such as “racial casting issues” (31) and the question of who sings, who can access an operatic career, and the kinds of audiences these works are reaching are foregrounded. This is vital work, but the format of the volume as a whole precludes analysis that can deeply grapple with the magnitude and complexity of the issues under discussion. Nonetheless, Clarke’s chapter offers a chance to expand on the issues raised by the Hutcheons, namely the perennial “problem” of jazz-opera. Under the subtitle “Québécité: Multiculturalism or Miscegenation?,” Clarke examines wide-ranging critiques of the opera: from the perception that a “jazz opera” is oxymoronic, to charges of generic instability (“chaotic mixing of style and form” [198]), he takes the opportunity to defend his work. The notion of jazz idioms as a contested element in opera is by no means an issue unique to Québécité, but is central to the discourse around a great deal of opera in North America of recent years that continues to push against—even dissolve—genre boundaries. Clarke’s answer to critics that struggled with the rich variety of linguistic, dramatic, and musical styles in Québécité confronts precisely the contested space of opera, a genre that continues to exhibit inherently exclusionary practices, reflecting wider concerns with integration, assimilation, and identity that are fundamental to his academic and literary writing and to discourses of contemporary opera generally. Mary Ingraham’s essay “The Other Within: Negotiating Musical Citizenship in Canadian Opera” is, like the Hutcheons’ and Clarke’s chapters, one of the more successful contributions in that it concretely engages the book’s central themes. In examples ranging from the early 1900s to the twenty-first century, Ingraham explores shifting approaches to the presence of First Nation narratives and musics in Canadian opera, considering issues such as the “ownership of cultural materials” (72). She charts significant changes, from the presence of indigenous peoples in pre-World War I operas as “exotic” curiosities, to the greater availability of source material post-World War II. Associations between her lines of inquiry and Constant’s work in the above-mentioned passage from the introduction readily emerge. By evaluating the different strategies of representing and articulating indigenous narratives on stage as juxtaposition versus integration (and everything in between), Ingraham directly engages with Constant’s overriding of the diversity/unity binary. Perhaps because Canada’s national multicultural framework is acutely primed for investigations of this kind, Ingraham’s contribution is apt and thoroughly consistent with the apparent intentions of the book. Characterizing three historical periods of Canadian opera as roughly assimilation, integration, and individuation, she posits these as parallel to evolving sociopolitical concerns and ideologies, thereby establishing a direct link between operatic culture and understandings of multiculturalism and coloniality in lived experience. Similar questions of musical and non-musical racial identity and hybridity are central to Nancy Rao’s essay “From Chinatown Opera to The First Emperor: Racial Imagination, the Trope of ‘Chinese Opera’ and New Hybridity” and Josh Stenberg’s account in chapter 9 of the infamous 1998 staging of Puccini’s Turandot in mainland China. Rao’s analysis both builds on familiar notions of orientalism and moves beyond discussing the now-familiar exoticist representations and processes of Othering in opera. Of particular note is her focus on male gendered racial otherness, which offers a fascinating counterpart to the many excellent studies on female “Oriental” Others in Madama Butterfly, Turandot, Lakmé, and more. At first tracing the understudied history of exoticist spectacle of Chinatown operas from the mid-nineteenth century onwards, Rao explores manifestations of a specifically male Chinese Other through to Tan Dun’s 2006 opera The First Emperor. Focusing on the opera’s critical reception, she also examines Tan Dun’s positionality and personal investment in the work, especially in its relationship with its Puccinian forebear. A more thorough evaluation of the reception of The First Emperor might have been expected, as discussions have often criticized the composer (rightly or wrongly) for the representation of Chinese identity and music, taking the guise of a “selling out” narrative by centering on ways the work plays into the exoticist fantasies of a venerable institution. While Rao’s essay offers an interesting expanded historical framework within which contemporary works in this vein might be assessed, it would benefit from greater attention to the diversity of perspectives surrounding contemporary reception issues. The final essay in part one, Nicholas Vazsonyi’s chapter “Playing the Race Card,” offers a succinct, historically grounded analysis of Wagner’s “particular brand of anti-Semitism” (84), using analogies from contemporary advertising practices to revise commonly held conceptions about the composer’s writings. Beyond the obvious, it is difficult to see how the essay, albeit well-written and nuanced in its analysis, successfully responds to the leading ideas of the volume. Offering a new perspective on well-worn Wagnerian ground may be valuable, but it strikes one as not a pressing concern in this context. Indeed, the volume is noticeably heavy with Wagner, with two further chapters following in part two, the largest section. The case studies in part two cover considerable historical ground (Haydn, Wagner, Puccini, and Strauss), although their outcome is largely a broadening and enriching of scholarship on thoroughly canonical composers, incorporating innovative sociological and historical perspectives on familiar repertoire. The analysis of how opera’s multiculturality might manifest focuses, in this conceptual model, on the coexistence of multiple productions: those which emphasize conflicts of power and identity, and those which challenge or subvert them. Chapters 8 and 10 tackle this in part by considering several different performance contexts of Wagner’s works. Essays by David Dennis and Frances Henry evaluate the use of Wagner’s music for the “popular” (i.e. non-expert) audiences for Nazi propaganda and the problematic 2003 production of Parsifal directed by Christoph Schlingensief at Bayreuth, respectively. Caryl Clark examines anti-Semitism in Haydn’s 1768 opera Lo speziale (The Apothecary), noting that it “indulged the prince’s [Nicolaus Esterházy] predilection for comedy redolent of Jewish caricature” (99). Sander Gilman offers a fascinating insight into Strauss’ Salomé from within the context of science and “scientific” racism in the early twentieth century, focusing on the assertion that the opera’s “contemporary reception was shaped by that representation of difference labeled ‘perversion’ ” (125). As beneficial as these case studies are for the history of anti-Semitism on the stage and in operatic and cultural discourse, they occupy such a significant proportion of the volume that the reader is left with a narrower sense of the guiding ideas of the book than might be desired. Reading familiar and less-familiar works against the grain is indisputably a valuable counterpoint to traditional narratives on some of opera’s unassailable heavyweights. As the editors’ introduction states, the collection “strives to explore the intricate interplay of cultural values and beliefs in Western opera through a critical examination of its origins, subsequent transformations, and the discourse generated from past and present performance practices” (8-9). Submitting the canon at large to a similar process of rereading, to enact the creating of alternative histories, is a valuable enterprise. Yet with so much of the volume dedicated to the reliable cornerstones of the genre, to what extent is the cultural lens—Western, Eurocentric—through which the book assesses experiences and representations of the multicultural simply reinforced further? I do not discredit the intellectually stimulating work presented here, and I am not implying that the authors stick to worn-out formulae. Developing novel analytical approaches to canonic repertoire is an absolute necessity in modern academia and the collection demonstrates several useful strategies to do so. But what of the objects of study? Where might we look beyond the “interplay of cultural values and beliefs in Western opera”? The “multicultural world” of the book emerges as more restrictive than one might imagine, lacking a thorough interrogation of multiculturalism as a concept and how it might be variously applied to opera scholarship. This criticism should not detract from the many excellent contributions made here. It strikes me as a practical issue as well as a methodological one: opera scholarship needs a far greater critical mass of studies that offer such “alternative histories,” alongside theoretical and critical work on key concepts such as the multicultural or the colonial, and alongside ethnographic studies and performance studies. This collection clearly demonstrates that current opera scholarship has expanded in fascinating ways, giving greater consideration to the processes of listening, performance, and social agency, and to sociological topics such as diversity, access, and demographics. Theory can obscure as much as it illuminates, but when conceptually potent terms are the baseline of books such as this one, we need clearer approaches to positing these within the limited framework of a collected volume. The final chapter, titled “Constructing Operatic Racism in Postmodern Cultural Studies,” does tackle the question of the “colonialist legacy of racism in opera,” (244) but, like the introduction, offers very broad strokes of copious conceptual, ethical, methodological, and historical questions in only a few short pages. The opening remit of Opera in a Multicultural World is expansive and difficult to satisfy, with the first part succeeding far more in responding with clarity and proximity to the central concepts. The struggle in reading a volume like this one is paradoxical: it offers an enormously rich span of essays that somehow ends up seeming restricted, despite topics covering four centuries, multiple continents, and several different methodologies and disciplinary foci. It puts empirical sociological study alongside historical research and critiques from a librettist, an interdisciplinarity and methodological intersectionality that is to be lauded when it works. Here, these fascinating studies more often feel juxtaposed rather than conversant—which, we might ask, could well be a structural rather than an intellectual flaw. Perhaps new formats are needed for opera scholarship that explicitly seeks to place diverse voices in dialogue. It may seem persnickety to criticize what may seem an issue of mere practicality, but this paradoxical experience of reading the book as at once innovative and frustratingly canonic speaks to deeper methodological tensions in a field that is swelling in rapidly multiplying but not always coherent directions. The collection of essays presented here amply demonstrates the extent to which the field of opera scholarship will benefit from expanded horizons, in both subject, methodology and perspective. At the very least, it offers a clearly flexible model for similar collaborative work in the future that can only serve to embolden musical scholarship of all types. It is representative of vital progress made towards fostering new approaches to a genre which is interdisciplinary by nature, inviting a growing diversity of perspectives and methodologies to forge a genuine and considered dialogue. References André, Naomi. 2018. Black Opera: History, Power, Engagement. Urbana: University of Illinois Press. André, Naomi, Karen M. Bryan, and Eric Saylor, eds. 2012. Blackness in Opera. Chicago: University of Illinois Press. Clarke, George Elliott. 1997. “White Like Canada.” Transition 73: 98–109. ———. 1999. Beatrice Chancy. Victoria, B.C.: Polestar Book Publishers. ———. 2002. Odysseys Home: Mapping African-Canadian Literature. Toronto: University of Toronto Press. Clément, Catherine. 1988. Opera, Or the Undoing of Women. Translated by Betsy Wing. Minneapolis: University of Minnesota Press. Constant, Fred. 2000. Le Multiculturalisme. Paris: Flammarion. Domínguez, Pilar Cuder, and George Elliott Clarke. 2001. “On Black Canadian Writing: In Conversation with George Elliott Clarke.” Atlantis 23 (2): 187–200. Hutcheon, Linda. 1991. Splitting Images: Contemporary Canadian Ironies. Toronto: Oxford University Press. Hutcheon, Linda, and Michael Hutcheon. 1998. “Opera and National Identity: New Canadian Opera.” Canadian Theatre Review 96: 5–8. Karantonis, Pamela, and Dylan Robinson, eds. 2011. Opera Indigene: Re/presenting First Nations and Indigenous Culture. New York: Routledge. Purvis, Philip, ed. 2013. Masculinity in Opera: Gender, History, and New Musicology. New York: Routledge.